Fenomena Setting Up Pasar Tradisional Gambir Deli Serdang - M H Z Nasution; B Karsono; Fidyati (Jurnal MESIL (Mesin Elektro Sipil), 2023)
Deli Serdang is one of the districts in North Sumatra Province. The main potential of this regency is to make the district the main route for the distribution of animal and vegetable foodstuffs for the city of Medan. One of the most active trading centers in Deli Serdang is the Gambir traditional market area in Deli Serdang Regency. Located on the border of Deli Serdang Regency and Medan City, this market is the center point for buying and selling activities, as a means of distribution and expediting the process of distributing goods and service producers to various consumers around it. The research objective is to explore the influence and reveal the positive impact on the establishment of traditional markets. The research method used in this research is qualitative, with exploratory descriptive to study the cases to be studied by describing the variables and conditions of the location by means of interviews, observation and documentation. The results of the study show that there is an impact that occurs if setting up is used in the market. By using the results of a combination of movement (movement), touch (atmosphere), visual perception (vision / perspective) and thoughts (mindset).